Simplifying
2x + 6 = 4x + -2
Reorder the terms:
6 + 2x = 4x + -2
Reorder the terms:
6 + 2x = -2 + 4x
Solving
6 + 2x = -2 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
6 + 2x + -4x = -2 + 4x + -4x
Combine like terms: 2x + -4x = -2x
6 + -2x = -2 + 4x + -4x
Combine like terms: 4x + -4x = 0
6 + -2x = -2 + 0
6 + -2x = -2
Add '-6' to each side of the equation.
6 + -6 + -2x = -2 + -6
Combine like terms: 6 + -6 = 0
0 + -2x = -2 + -6
-2x = -2 + -6
Combine like terms: -2 + -6 = -8
-2x = -8
Divide each side by '-2'.
x = 4
Simplifying
x = 4